Biofuel and Biochemical Analysis of Amphora coffeaeformis RR03, a Novel Marine Diatom, Cultivated in an Open Raceway Pond - Muthu Ganesan Rajaram; Subramani Nagaraj; Manubolu Manjunath; Annakkili Baskara Boopathy; Chidambaram Kurinjimalar; Ramasamy Rengasamy; Thanasekaran Jayakumar; Joen-Rong Sheu; Jiun-Yi Li (Energies, 2018)
(1) Background: To increase the biochemical productivity and to reduce the production cost of microalgal biodiesel, this study aimed to investigate the effects of CO2 on biomass, fatty acids, carbon-hydrogen, and biochemical accumulation of the marine diatom, Amphora coffeaeformis RR03 (A. coffeaeformis) RR03. (2) Methods: Fatty acid composition of the dry biomass of A. coffeaeformis RR03 was analysed using Gas chromatography-mass spectrometry (GC-MS). (3) Results: The results showed that A. coffeaeformis RR03 contained high biomass productivity and biochemical composition in different cultivation conditions. A. coffeaeformis RR03 showed maximum growth of 5.2 × 106/mL on 21st day cultivation under CO2 supply. The bio-crude oil production from A. coffeaeformis RR03 was 36.19 megajoule (MJ). GC-MS analysis found that the dry biomass of A. coffeaeformis RR03 contained maximum of 47.72% fatty acids of 16-octadecanoic acid methyl ester (10:12) and 19.58% pentadecanoic acid, 13-methyl-, and methyl ester (9.24). (4) Conclusion: The results of this study may suggest that a novel diatom of A. coffeaeformis RR03 could be a suitable candidate for biocrude production in order to meet the future demand of energy.